2015
DOI: 10.1136/bjophthalmol-2015-307674
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a new rebound tonometer for self-measurement of intraocular pressure

Abstract: Sub-titleSelf-measurement using Icare Home showed good agreement with Goldmann applanation tonometry. Icare Home self-measurement was well accepted and reliable results obtained by 3 in 4 subjects, suggesting potential use for home measurement of intraocular pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
76
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(102 citation statements)
references
References 24 publications
(28 reference statements)
16
76
1
2
Order By: Relevance
“…We found a mean IOP difference between the GAT and icare ® Home measurements of 0.15 mmHg, similar to the results obtained in previous studies of patients with glaucoma (Dabasia et al. ; Chen et al. ; Termuhlen et al.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…We found a mean IOP difference between the GAT and icare ® Home measurements of 0.15 mmHg, similar to the results obtained in previous studies of patients with glaucoma (Dabasia et al. ; Chen et al. ; Termuhlen et al.…”
Section: Discussionsupporting
confidence: 91%
“…Self‐tonometry measurements made by patients with glaucoma using icare ® Home tonometers were evaluated in previous studies and found to agree well with GAT results (Dabasia et al. ; Chen et al. ; Termuhlen et al.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…The within measurement intra-class correlation coefficient (ICC) of Goldmann applanation tonometry and rebound tonometry were 0.98 (95% confidence interval (CI): 0.97–0.99) and 0.94 (95% CI: 0.90–0.96), respectively. Although rebound tonometer was showed may underestimate the IOP compared to Goldmann applanation tonometry measurements in previous studies,[32] We evaluated the correlation and agreement between patient-measured IOP using rebound tonometry with ophthalmologist-measured IOP using Goldmann applanation tonometry in our cohort, and found that both modes of IOP measurements correlated well with each other, a good agreement was also identified with a mean difference ± 1 standard deviation (SD) of 0.15 ± 0.65 mmHg ( p = 0.682) between Goldmann applanation tonometry and rebound tonometry. The between-measurement ICC of these two tonometries was 0.72.…”
Section: Discussionmentioning
confidence: 96%
“…Allerdings wird auch deutlich, dass die Übereinstimmung der Messwerte zwischen GAT und NCT deutlich besser ist, insbesondere außerhalb des Normbereichs. Dennoch erlaubt das Icare neben dem Einsatz bei Kindern oder anderen Patienten, bei denen eine Untersuchung an Spaltlampe oder mit NCT nicht möglich ist, inzwischen auch eine Selbsttonometrie durch den Patienten [3,4]. Somit ermöglicht dieses Gerät eine recht verlässliche Bestimmung des Augeninnendrucks und damit eine bessere Führung dieser Patienten.…”
Section: Fazitunclassified